Toward rational thermostabilization of Aspergillus oryzae cutinase: Insights into catalytic and structural stability. Issue 1 (26th November 2015) - Shirke, Abhijit N.; Basore, Danielle; Butterfoss, Glenn L.; Bonneau, Richard; Bystroff, Christopher; Gross, Richard A.
ABSTRACT: Cutinases are powerful hydrolases that can cleave ester bonds of polyesters such as poly(ethylene terephthalate) (PET), opening up new options for enzymatic routes for polymer recycling and surface modification reactions. Cutinase from Aspergillus oryzae (AoC) is promising owing to the presence of an extended groove near the catalytic triad which is important for the orientation of polymeric chains. However, the catalytic efficiency of AoC on rigid polymers like PET is limited by its low thermostability; as it is essential to work at or over the glass transition temperature ( T g ) of PET, that is, 70°C. Consequently, in this study we worked toward the thermostabilization of AoC. Use of Rosetta computational protein design software in conjunction with rational design led to a 6°C improvement in the thermal unfolding temperature ( T m ) and a 10‐fold increase in the half‐life of the enzyme activity at 60°C. Surprisingly, thermostabilization did not improve the rate or temperature optimum of enzyme activity. Three notable findings are presented as steps toward designing more thermophilic cutinase: (a) surface salt bridge optimization produced enthalpic stabilization, (b) mutations to proline reduced the entropy loss upon folding, and (c) the lack of a correlative increase in the temperature optimum of catalytic activity with thermodynamic stability suggests that the active site is locally denatured at a temperature below the T m of the global structure. Proteins 2016; 84:60–72. © 2015 Wiley Periodicals, Inc.